Dawr al-mu'assasat al-khayriyah fi dirasat'ilm al-siyasah fi al-Wilayat al-Muttahidah al-Amrikiyah : (Dirasat halat muassasat Furd 1950-2004) - al-Khaffaji, Riham Ahmad Mahrus; Amanah al-'Ammah lil-Awqaf (Kuwait) (al-Kuwayt : Idarat al-Dirasat wa-al-'Alaqat al-Kharijiyah, al-Amanah al-'Ammah lil-Awqaf, 2009)
Presents Ford Foundation in the context of its creation, its roles, its financing of higher education, sources and problems of education financing. The book also presents Ford Foundation as well-managed and famous organization in both the United States and the world for its outstanding performance and its support of research.
al-Fasl al-rabi': Muassasat Furd wa-al-'alaqat al-dawliyah. al-Mabhath al-awwal: Dirasat al-amn al-dawli -- al-Mabhath al-thani: Dirasat al-siyasah al-kharijiyah al-amrikiyah -- al-Mabhath al-thalith: Dirasat al-qanun al-dawli wa-al-munazzamat al-dawliyah --- al-Fasl al-khamis: Muassasat Furd wa-dirasat al-manatiq. al-Mabhath al-awwal: Aba'ad wa-istiratijiyat da'm dirasat al-manatiq: al-bu'd al-muassasi -- al-Mabhath al-thani: Aba'ad wa-istiratijiyat da'm dirasat al-manatiq: al-ab'ad al-bashariyah wa-al-ma'lumatiyah wa-al-tafa'ul al-dawli -- al-Mabhath al-thalith: al-Qadaya al-mumawwalah fi majalat dirasat al-manatiq --- al-Khatimah.
Includes bibliographical references.
Keywords: Ford Foundation -- Education (Higher) -- United States -- Endowments; Ford Foundation; Education, Higher -- United States; Universities and colleges -- United States -- Endowments; Benefactors -- Charitable contributions -- United States; Education, Higher -- United States -- Finance; Political science -- Study and teaching (Higher) -- United States